2020
DOI: 10.3390/su12020721
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Landscapes on Water Quality in A Typical Headwater Catchment, Southeastern China

Abstract: The relationship between land landscape and water quality has been a hot topic, especially for researchers in headwater catchment, because of drinking water safety and ecological protection. In this study, Lita Watershed, a typical headwater catchment of Southeast China, was selected as the study area. During 2015 and 2016, water samples were collected from 18 sampling points every month, and 19 water quality parameters were tested such as nutrients and heavy metals. Through multistatistics analysis, the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…For example, we found that the connectedness of the industrial land, dominances and fragmentations of the road and urban greenspace, and the fragmentation of the under construction land were correlated with the concentrations of TN and TP in the stream water. By identifying the influential land uses and the corresponding landscape pattern metrics, it might be possible to artificially influence water quality by optimizing the composition and spatial pattern of the specific land uses [79,80].…”
Section: Influence Of Landscape Patterns On Water Qualitymentioning
confidence: 99%
“…For example, we found that the connectedness of the industrial land, dominances and fragmentations of the road and urban greenspace, and the fragmentation of the under construction land were correlated with the concentrations of TN and TP in the stream water. By identifying the influential land uses and the corresponding landscape pattern metrics, it might be possible to artificially influence water quality by optimizing the composition and spatial pattern of the specific land uses [79,80].…”
Section: Influence Of Landscape Patterns On Water Qualitymentioning
confidence: 99%
“…Several research groups studied the relationships between several influencing factors and water quality. Zhao et al [ 18 ] analyzed the impact of landscapes on water quality in a typical headwater catchment of Southeast China by using canonical correlation analysis (CCA) and found that land use patterns in the surrounding areas had an indirect impact on the concentration and migration of pollutants. Scheili et al [ 19 ] studied the impact of climate factors on water quality by using regression analysis.…”
Section: Introductionmentioning
confidence: 99%